Wpływ kapitału zagranicznego na zmiany struktury rynku w polskim przemyśle przetwórczym - Kozłowska, Anna; Szczepkowska-Flis, Agnieszka (The Influence of Foreign Capital on Market Structural Changes in Polish Manufacturing, 2009)
The aim of the study was to estimate the impact of foreign capital on market structural changes in Polish manufacturing between 1997 and 2007. Branches of Polish manufacturing were divided into two sectors: of high and low market concentration. The level of foreign capital was measured by indicator KZ, calculated as the ratio of foreign capital to core capital. Market structural changes were measured by two indicators: coefficient Q and Gini concentration coefficient G. Econometric analyses showed that in both sectors foreign capital limited the intensity of market structural changes measured by coefficient Q. There were no statistically significant relations between foreign capital and Gini concentration coefficient G in any of the analyzed sectors. Our results indicate that in the analyzed years foreign capital stabilized economic structure through reducing changes of firms' population.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 670-679